2008
DOI: 10.1080/17408980701345550
|View full text |Cite
|
Sign up to set email alerts
|

Non-specialist teachers' confidence to teach PE: the nature and influence of personal school experiences in PE

Abstract: Background: Over the past 20 years, a number of researchers have expressed concern over the lack of confidence and qualifications of primary school teachers to teach PE. Evidently, the influence of personal school PE experiences may play an important role in the development of teachers' confidence to appropriately teach PE. Most research that has examined the effects of biographical experiences in PE on teachers' confidence teaching PE has focused on specialist, rather than non-specialist PE teachers. Purpose:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
177
2
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(204 citation statements)
references
References 40 publications
12
177
2
13
Order By: Relevance
“…66,67 Therefore, schools should ensure FMS lessons are delivered in a pedagogically appropriate manner 60 and that PE specialists are engaged. Given that the primary school years are considered the optimal time to develop FMS 4 and current issues with FMS learning contexts in primary schools, 68 training and resources need to be prioritized so that children can receive quality instruction. Researchers and education authorities may also need to consider the adoption of evidence-based programs and determine how these could be translated and sustained without researcher support.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…66,67 Therefore, schools should ensure FMS lessons are delivered in a pedagogically appropriate manner 60 and that PE specialists are engaged. Given that the primary school years are considered the optimal time to develop FMS 4 and current issues with FMS learning contexts in primary schools, 68 training and resources need to be prioritized so that children can receive quality instruction. Researchers and education authorities may also need to consider the adoption of evidence-based programs and determine how these could be translated and sustained without researcher support.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Furthermore, the role of PE as 'a core activity linked to healthy lifestyles, lifelong learning, improved health, an inclusive society' (Scottish Executive, 2004a, p. 2) has been emphasised in the new curriculum by requiring two hours or two periods per week of PE for every pupil in Scotland between 5 and 16 years of age (p. 10). These recent policy and curricular developments bring into focus the significance of professional growth and teacher development in general, particularly in primary PE where it was found that teachers lack the knowledge, skills and confidence to teach PE due to the limited subject input in primary ITE (Blair & Capel, 2011;Elliot et al, 2011;Morgan & Bourke, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Skilful and successful pupils are more likely to have positive PE experiences (Callea et al, 2008) linked to participating in teams, praise and experiences of success and competence (Pickup, 2005). PE experiences affect the formation of PCTs' predispositions about teaching PE and later the quality of their teaching practices (Matanin & Collier, 2003;Morgan & Bourke, 2008) through teaching confidence, perceived teaching competence and attitudes towards teaching PE (Chedzoy, 2000;Morgan & Bourke, 2008;Morgan & Hansen, 2008;Webster, 2011). In the contrary, negative PE experiences may lead to not valuing PE as a school subject, avoidance of teaching diverse skills or teaching PE at all, favouring the non-teaching strategy or forwarding the negative experiences to their own pupils (Morgan & Hansen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the contrary, negative PE experiences may lead to not valuing PE as a school subject, avoidance of teaching diverse skills or teaching PE at all, favouring the non-teaching strategy or forwarding the negative experiences to their own pupils (Morgan & Hansen, 2008). Teachers may also try to avoid repeating the negatively experienced models and instead to forward the positive ones (Morgan & Bourke, 2008;Morgan & Hansen, 2008;Murphy & Cosgrave, 2010;Pickup, 2005). The negative experiences may also increase teachers' sensitivities for observing and taking into consideration the needs of pupils with lower levels of physical competence (Allen, 2003;Allen, 2005;Morgan & Hansen, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation